Hemorrhage and venous thromboembolism in critically ill patients with COVID-19. (May 2021) - Qiu, Chenyang; Li, Tong; Wei, Guoqing; Xu, Jun; Yu, Wenqiao; Wu, Ziheng; Li, Donglin; He, Yangyan; Chen, Tianchi; Zhang, Jingchen; He, Xujian; Hu, Jia; et al.
Objective: The majority of patients with COVID-19 showed mild symptoms. However, approximately 5% of them were critically ill and require intensive care unit admission for advanced life supports. Patients in the intensive care unit were high risk for venous thromboembolism and hemorrhage due to the immobility and anticoagulants used during advanced life supports. The aim of the study was to report the incidence and treatments of the two complications in such patients. Method: Patients with COVID-19 (Group 1) and patients with community-acquired pneumonia (Group 2) that required intensive care unit admission were enrolled in this retrospective study. Their demographics, laboratory results, ultrasound findings and complications such as venous thromboembolism and hemorrhage were collected and compared. Results: Thirty-four patients with COVID-19 and 51 patients with community-acquired pneumonia were included. The mean ages were 66 and 63 years in Groups 1 and 2, respectively. Venous thromboembolism was detected in 6 (18%) patients with COVID-19 and 18 (35%) patients with community-acquired pneumonia (P = 0.09). The major type was distal deep venous thrombosis. Twenty-one bleeding events occurred in 12 (35%) patients with COVID-19 and 5 bleeding events occurred in 5 (10%) patients with community-acquired pneumonia, respectively (P = 0.01). Gastrointestinal system was the most common source of bleeding. With the exception of one death due to intracranial bleeding, blood transfusion with or without surgical/endoscopic treatments was able to manage the bleeding in the remaining patients. Multivariable logistic regression showed increasing odds of hemorrhage with extracorporeal membrane oxygenation (odds ratio: 13.9, 95% confidence interval: 4.0–48.1) and COVID-19 (odds ratio: 4.7, 95% confidence interval: 1.2–17.9). Conclusion: Venous thromboembolism and hemorrhage were common in both groups. The predominant type of venous thromboembolism was distal deep venous thrombosis, which presented a low risk of progression. COVID-19 and extracorporeal membrane oxygenation were risk factors for hemorrhage. Blood transfusion with or without surgical/endoscopic treatments was able to manage it in most cases.